(untitled) (International Journal of Food and Nutritional Sciences, 2024)
With the incline of modern-day computing and technology, most businesses and establishments may adapt and embrace these changes as it improves their work, lives, and provides more accurate and reliable results in the end and the miss using of Funds and the citizens not being aware of schemes and the ongoing work progress of their respective areas. The E-PANCHYAT is a comprehensive digital plat-form designed to facilitate the management and development of rural communities and for digitalizing the manual data into a proper manner and which facilities for the local governance system in the future days and as well as proper usage of the available resources and giving awareness about the latest schemes and reporting the problems in their respective panchayat about the miss use of funds or any other issues in the gram panchayat and user can able to raise a complaint against the head of the village or any authorized person who is miss using the login access of the system. The projectheading towards a digital Telangana by updating the each and individual resources and items in the village and the E-PANCHYAT evaluates in different phases based on the requirement of the Village and it consists of population data, family details, schemes, funds, resources and more over it also includes the literacy rate and voters count of the Villages and the data of villages are monitored by the higher authorities. This front-end of the project is developed using HTML, CSS, JavaScript and back-end technologies like PHP and MySQL database.